PEMODELAN MATEMATIKA PADA PROSES PEMBEKUAN ES DI RUANG BRINE TANK PABRIK ES BALOK TALANGSARI JEMBER - Sholihin, Akhmad; Fatahillah, Arif; Setiawan, Toto' Bara (Kadikma, 2019)
One of the main activities of block ice production is the process of freezing ice blocks in the brine tank. Brine Tank is a tank that functions to freeze ice blocks. Brine Tank contains salt water. Mathematical modeling is a formulation of mathematical models that describe how to get a solution to a mathematical problem in a natural event. Mathematical modeling can form mathematical models that describe the process of ice freezing in brine tanks in accordance with actual conditions without ignoring important factors in the system. The mathematical model in the process of ice freezing in the Brine Tank is obtained from the momentum equation and the energy equation which is solved using the finite volume method. In this study a mathematical model was built to determine the effectiveness of time in the ice freezing process in the brane tank.